Spectrophotometric Estimation of Metadoxine in Oral Solid Dosage Forms - Abirami, G.; Vaidhyalingam, V.; Niraimathi, V.; Aruna, Ajithadas (Asian Journal of Chemistry, 2010)
Three new, simple sensitive and reproducible spectrophotometric methods have been developed for the estimation of metadoxine in oral solid dosage form, (method A, B and C). Method A obeys Beer's law in concentration ranging from 8-64 μg/mL and exhibiting maximum absorption at 291 nm. Method B obeys Beer's law in the same concentration from 8-64 μg/mL. By derivatising the primary spectra the second derivative spectrum is obtained. Method C is difference spectroscopy method which is based on shifting the λmax by changing the pH of the solution, by adding 0.1 M HCl and 0.1 M NaOH. This produces maximum absorption at 309, 245 and 290 nm. At 245 nm, it obeys Beer's linearity in concentration ranging from 8-64 μg/mL. The methods were extended upto pharmaceutical formulations and there was no interference from any common excipients and diluents. The results of analysis have been validated statistically by recovery studies.